Manajemen Strategis Situs Cagar Budaya Nasional Pugung Raharjo: Analisis Research Gap Periode 2020-2025 - Roliyanti Roliyanti; Kuncoro Budi Riyanto; Febriyanto Febriyanto (Jayapangus Press, 2026)
The Pugung Raharjo National Cultural Heritage Site is a multidimensional cultural heritage asset that necessitates a robust research framework to support its protection and sustainable utilization. However, its strategic management challenges still require a scientific, data-based evaluation, potentially leading to redundancies and the neglect of critical management issues. This study aims to map trends, disciplinary characteristics, and methodological gaps, including identifying research gaps at the Pugung Raharjo National Cultural Heritage Site for the 2020-2025 period as a basis for formulating strategic management recommendations. The method used was a Systematic Literature Review (SLR) of 22 published articles obtained from various journal databases and institutional repositories. The results show a dominance of publications in the education sector (40.9%) and tourism management (31.8%), but very little on the technical physical conservation aspect (18.2%). Methodologically, there was a high reliance on qualitative approaches and R&D, while purely quantitative methods were found at only 13.6%. The novelty of this study lies in its position as the first SLR-based strategic reference that synthesizes multidisciplinary data to become the basis for policy-making for national cultural heritage management. These findings indicate a research gap in statistical data auditing and technical physical monitoring of sites. This study recommends a reorientation of strategic management through the formalization of local education curricula, the implementation of tourism carrying capacity, and the digitization of conservation data to ensure the sustainability of sites, as mandated by Law No. 11 of 2010 concerning Cultural Heritage.